2012
DOI: 10.1002/clc.22042
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Endothelial Functions and Acetylsalicylic Acid Resistance in Newly Diagnosed Hypertensive Patients

Abstract: Background: We aimed to investigate the effects and dose dependency of aspirin on endothelial functions and prevalence of aspirin resistance in newly diagnosed hypertensive patients without previous drug therapy and development of cardiac complications. Hypothesis: Acetylsalicyclic acid improves endothelial function. Methods: Fifty-eight hypertensive patients and 61 healthy subjects in the control group were included in the study. Endothelial functions of the patient and control groups were evaluated with brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…There are contradictory studies on the relation of aspirin with hypertension in the literature. In 2 separate studies—in newly diagnosed patients and patients with chronic hypertension—there was no relationship between AR and hypertension, 17,18 whereas the presence of hypertension in patients with stable coronary artery was found as predictive of AR. 19 In our study, ABPM was performed in all patients, and mean/daytime/nighttime SBP and night time DBP was higher in patients with AR.…”
Section: Discussionmentioning
confidence: 88%
“…There are contradictory studies on the relation of aspirin with hypertension in the literature. In 2 separate studies—in newly diagnosed patients and patients with chronic hypertension—there was no relationship between AR and hypertension, 17,18 whereas the presence of hypertension in patients with stable coronary artery was found as predictive of AR. 19 In our study, ABPM was performed in all patients, and mean/daytime/nighttime SBP and night time DBP was higher in patients with AR.…”
Section: Discussionmentioning
confidence: 88%
“…34 In hypertensive patients, basal NO activity is decreased and endothelium-dependent vasodilation in response to acetylcholine is impaired in forearm circulation. 31,35,36 Sahin et al 31 have found that endothelial functions were improved in hypertensive patients after treatment with ASA. The benefit of antiplatelet therapy with ASA in patients with hypertension is well established, and it has been suggested that ASA modulates acetylcholine-induced peripheral vasodilation in patients with atherosclerosis, possibly via inhibition of 1 or more COX-dependent vasoconstrictors.…”
Section: Discussionmentioning
confidence: 98%
“…31,32 Oxidative stress and endothelial dysfunction are consistently observed in hypertensive patients; however, emerging evidence suggests that they also have a causal role in the molecular processes leading to hypertension. ASA is a potent antioxidant agent, and reduction in vascular production of superoxide in normotensive and hypertensive rats has been demonstrated previously.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Presence or greater severity of hypertension, visceral obesity, low high density lipoprotein cholesterol and/or high triglyceride values, insulin resistance, kidney disease, elevated CRP levels, and endothelial dysfunction amplify cardiometabolic risk in most instances. Obesity,[10] hypertension,[11] diabetes,[12] dyslipidemia, high CRP levels,[13] and other individual risk factors/biomarkers are connected with antiplatelet drug resistance. These data suggest that, although such resistance frequently occurs in patients without MetS, additional features that intensify the thrombotic, inflammatory, and hyperglycemic burdens, particularly those that thwart availability of nitric oxide through potent prooxidative mechanisms, may increase the likelihood of antiplatelet drug resistance.…”
mentioning
confidence: 99%